MENJAGA KESEHATAN SANTRI: UPAYA PHBS SEBAGAI PENCEGAHAN DIARE DI LINGKUNGAN PONDOK PESANTREN - Fitriani, Rani; Mesi Setiana, Eva (Jurnal LENTERA, 2024)
Clean and Healthy Living Behavior (PHBS) plays a crucial role at Pondok Pesantren Walisongo Kotabumi, with a focus on preventing the risk of diarrhea. The community service project aims to enhance awareness and implementation of PHBS among 30 students aged 6-7 years. Involving evaluation instruments such as structured questions, interviews, and participatory observations, the activity took place on October 7, 2023. The material includes PHBS techniques, smart decision-making, and responsible PHBS implementation. Evaluation indicates a significant increase in students' knowledge (100%) regarding "PHBS Efforts as Diarrhea Prevention in the Pondok Pesantren Environment." Positive participant responses reflect satisfaction with the material, and action evaluation shows a positive impact of the program on the implementation of PHBS among students, contributing positively to the well-being and stability of the pesantren environment